A Two‐Photon Luminescent Dye‐Loaded Metal–Organic Framework for Physiological Temperature Sensing within Biological Windows. Issue 11 (15th November 2017) - Wan, Yating; Xia, Tifeng; Cui, Yuanjing; Yang, Yu; Qian, Guodong
Abstract: Luminescent temperature sensing in biological windows is uniquely superior compared to traditional temperature sensing methods because the scattering and absorption by skin, tissue and blood is minimal. In this study, the two‐photon luminescence from dyes loaded into a metal–organic framework was utilised to achieve physiological temperature sensing within two biological windows. A composite was prepared that can be excited at 1064 nm to emit at 650 nm, well within the two biological windows. The two‐photon luminescence intensity at 650 nm has a linear relationship with temperature over the range 20 to 60 °C. In addition, the stability and quantum efficiency were significantly improved after loading into the MOF and, with high temperature resolution, excellent repeatability and low biological toxicity, measurements with this composite has great potential to be applied to physiological temperature sensing in cells or tissues. Abstract : Window of opportunity : A two‐photon luminescent dye‐loaded metal–organic framework, ZJU‐28⊃ DPASD, with excitation and emission bands within biological windows, was prepared (see figure). The composite showed outstanding physiological temperature‐sensing performance in the range 20 to 60 °C with low cytotoxicity and high stability, and is promising for application in cells or tissues.